2021
DOI: 10.1172/jci.insight.147982
|View full text |Cite
|
Sign up to set email alerts
|

HuR/Cx40 downregulation causes coronary microvascular dysfunction in type 2 diabetes

Abstract: Patients with diabetes with coronary microvascular disease (CMD) exhibit higher cardiac mortality than patients without CMD. However, the molecular mechanism by which diabetes promotes CMD is poorly understood. RNA-binding protein human antigen R (HuR) is a key regulator of mRNA stability and translation; therefore, we investigated the role of HuR in the development of CMD in mice with type 2 diabetes. Diabetic mice exhibited decreases in coronary flow velocity reserve (CFVR; a determinant of coronary microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…Coronary microvascular function was determined by assessment of coronary flow velocity reserve (CFVR). 14,16 Coronary blood flow velocity (CFV) was measured by echocardiography using a Vevo2100 system (FUJIFILM Visual Sonics, Inc., Toronto, Canada). Mice were anesthetized with isoflurane (1%), and the resting level of CFV was obtained.…”
Section: Animalsmentioning
confidence: 99%
“…Coronary microvascular function was determined by assessment of coronary flow velocity reserve (CFVR). 14,16 Coronary blood flow velocity (CFV) was measured by echocardiography using a Vevo2100 system (FUJIFILM Visual Sonics, Inc., Toronto, Canada). Mice were anesthetized with isoflurane (1%), and the resting level of CFV was obtained.…”
Section: Animalsmentioning
confidence: 99%
“… 34 Associations have been observed between three RNA‐binding proteins and insulin resistance; therefore, increased type 2 diabetes risk. 35 , 36 Hence, the authors hypothesized an association between elevated RNA‐binding protein subunit (#38) levels and diabetic renal complications in T1DM patients with DN. 37 …”
Section: Rbps In Diabetic Nephropathymentioning
confidence: 99%
“…RNA‐binding protein regulatory subunit 38, also known as Protein DJ‐1, is likely to be significantly more abundant in T1DM patients with DN due to specific mRNAs stabilization, a process by which cells may control protein expression levels 34 . Associations have been observed between three RNA‐binding proteins and insulin resistance; therefore, increased type 2 diabetes risk 35,36 . Hence, the authors hypothesized an association between elevated RNA‐binding protein subunit (#38) levels and diabetic renal complications in T1DM patients with DN 37 …”
Section: Rbps In Diabetic Nephropathymentioning
confidence: 99%
“…In addition to endothelial cell dysfunction, diabetic vascular disease can further alter capillary density to affect coronary flow velocity reserve (CFVR), which in turn develops into coronary microvascular disease (CMD) ( Si et al, 2021 ). Previous research showed that HuR overexpression promotes angiogenesis via stabilizing VEGF-A mRNA and modifying endothelial cell angiogenic activity ( Chang et al, 2013 ).…”
Section: Rbps and Diabetic Complicationsmentioning
confidence: 99%
“…In addition, diabetes attenuates the expression of Cx40, a gap junction channel protein, in cardiac ECs and impairs coronary microvascular function via downregulating the level of RNA-binding protein HuR. Overexpression of CX40 increased the density of capillary and ameliorated CFVR in diabetic mice ( Si et al, 2021 ).…”
Section: Rbps and Diabetic Complicationsmentioning
confidence: 99%